Lymphoedema in the aspect of breast cancer treatment – pathogenesis, principles of treatment, and prophylaxis - Lipińska, Anna M. (Medical Studies/Studia Medyczne, 2015)
Secondary lymphoedema is a complication after oncological treatment. Rehabilitation management is aimed at reducing lymph stasis and improving mobility. Long-lasting lymphoedema can cause changes in the bones and joints. Increasing oedema significantly restricts the mobility of joints, and after some time leads to degenerative changes. Progressive changes in the appearance and function of the limb also cause emotional and mental changes. The problem of lymph stasis in patients after mastectomy is very serious and requires an appropriate early implementation of physiotherapy. Applied physiotherapeutic methods can be used in an independent or associated way. Currently, treatment of lymphoedema is based on symptom treating, so the knowledge of the lymphoedema pathogenesis can significantly contribute to the patients’ awareness of the need to apply antiedematous prophylaxis.